International and Scientific Activities of the Lithuanian Road Administration are the Source of Experience - Skirmantas Skrinskas (The Baltic Journal of Road and Bridge Engineering)
International cooperation and close relations with scientific institutions assist the Lithuanian Road Administration under the Ministry of Transport and Communications of Lithuania in implementing the policy of road network development, road building and maintenance, infrastructure development, and traffic safety organization. Fostering of cooperation in the region and abroad, exchange of best practices, improvement of professional skills, also the scientific research works and studies and dissemination of their results play an important role in the improvement of road infrastructure. The article outlines representation of Lithuanian Road Administration in international road organizations and the main fields of its scientific activities and research.